SOB A SOMBRA DO ATOR: A formação e treinamento do ator no Teatro de Sombras. - Freitas Filho, Welerson (2018)
This research proposes to study the process of formation and training of the actor in the Shadows Theater as well as to identify the fundamentals and principles necessary for the work with the language. For this research, which is exploratory and qualitative, two procedures were approached: bibliographical research focusing on the study of Shadows Theater, the formation of the actor in the Puppertry and the practices and concepts of actor training in the 20th Century and 21th; and the case study of Cia. Karagözwk (PR) and Cia. Lumiato (DF) that work specifically with the artistic modality of the Shadow Theater. Investigations and dialogues about the formation and training procedures addressed by the two companies result in a collaborative study to fill gaps in theatrical studies of the actor's work.